Acute and chronic wound fluids inversely influence adipose‐derived stem cell function: molecular insights into impaired wound healing. Issue 1 (13th March 2013) - Koenen, Paola; Spanholtz, Timo A; Maegele, Marc; Stürmer, Ewa; Brockamp, Thomas; Neugebauer, Edmund; Thamm, Oliver C
Abstract Wound healing is a complex biological process that requires a well‐orchestrated interaction of mediators as well as resident and infiltrating cells. In this context, mesenchymal stem cells play a crucial role as they are attracted to the wound site and influence tissue regeneration by various mechanisms. In chronic wounds, these processes are disturbed. In a comparative approach, adipose‐derived stem cells (ASC) were treated with acute and chronic wound fluids (AWF and CWF, respectively). Proliferation and migration were investigated using 3‐(4, 5‐Dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide (MTT) test and transwell migration assay. Gene expression changes were analysed using quantitative real time–polymerase chain reaction. AWF had a significantly stronger chemotactic impact on ASC than CWF (77·5% versus 59·8% migrated cells). While proliferation was stimulated by AWF up to 136·3%, CWF had a negative effect on proliferation over time (80·3%). Expression of b‐FGF, vascular endothelial growth factor (VEGF) and matrix metalloproteinase‐9 was strongly induced by CWF compared with a mild induction by AWF. These results give an insight into impaired ASC function in chronic wounds. The detected effect of CWF on proliferation and migration of ASC might be one reason for an insufficient healing process in chronic wounds.